THE ASSOCIATION BETWEEN CHRONONUTRITION BEHAVIOUR AND CONSUMPTION LEVELS WITH THE OCCURRENCE OF CENTRAL OBESITY AMONG BUMN OFFICE EMPLOYEES IN CIANJUR - Ramadina, Wyanda Aurellia; Insani, Hurry Mega; Sentani, Muchamad Rizki; Rosdiana, Delita Septia (HEARTY, 2026)
Central obesity is considered more harmful because it is associated with an increased risk of disease. In Indonesia, the prevalence of central obesity almost doubled from 18.8% in 2007 to 31% in 2018, while in Cianjur Regency it increased from 15.7% in 2007 to 23.8% in 2013. BUMN office workers represent one of the groups with the highest prevalence of central obesity (50.1%). Factors influencing central obesity include sex, education level, macronutrient intake, and chrononutrition behaviour. Objective: To examine the association between chrononutrition behaviour and consumption levels with central obesity. Methods: This quantitative cross-sectional study involved 60 participants selected using simple random sampling. Data were collected through waist circumference measurement, Chrononutrition Profile Questionnaire (CPQ), and 2×24-hour dietary recalls. Data analysis was performed using IBM SPSS Statistics 21 with the Chi-square test. Results: Breakfast skipping and short evening latency were significantly associated with central obesity (p < 0.05), while eating window, evening eating, night eating, and largest meal showed no significant association (p ≥ 0.05). Energy and carbohydrate intake levels were significantly associated with central obesity (p < 0.05), whereas protein and fat intake levels were not (p ≥ 0.05). Conclusion: Office employees are encouraged to avoid skipping breakfast, limit late-night eating, and maintain balanced energy and carbohydrate intake to reduce the risk of central obesity.